CLINICAL CASE OF CONGENITAL DIAPHRAGMATIC HERNIA - Исаханян, Аида Анушавановна; Колмакова, Наталья Юрьевна; Кляшторная, Олеся Владимировна; Царюк, Елена Павловна; Головкина, Надежда Владимировна; Маисеенко, Дмитрий Александрович (Mother and Baby in Kuzbass, 2023)
Despite current advances in obstetrics and pediatric surgery, the survival rate of newborns with congenital diaphragmatic hernia does not exceed 50 %. This article describes a clinical case of a child with congenital diaphragmatic hernia with a favorable outcome after timely surgical correction. In our clinical case, the absence of prenatal diagnostics (lack of diagnosis and dynamic monitoring during gestation – late appearance of the pregnant woman in the antenatal clinic), but early postnatal diagnosis allowed for effective surgical correction of this congenital malformation in the newborn.